A study of wild medicinal plants used in Nargu Wildlife Sanctuary of district Mandi in Himachal Pradesh, India - Radha, Pallavi Chauhan, Sunil Puri, Mamta Thakur, Sonia Rathour, Abhishek Kumar Sharma, Ashok Pundir (Journal of Applied Pharmaceutical Science, 2021)
The current study was carried out from 2019 to 2020 to collect data on the use of wild ethnomedicinal plants in Nargu Wildlife Sanctuary of district Mandi in Himachal Pradesh, India. Information on wild medicinal plants for this survey was collected through personal field visits, interviews, discussion, and a pre-tested questionnaire. A total of 45 plant species, belonging to 28 different families were identified, along with their botanical name, vernacular name, family, and habitat. Of the identified species, most were herbs and shrubs (16), followed by trees (6), climbers (5), and ferns (2). The leaves were the most common part used in the medicinal preparations. The largest number of plant species were from Rosaceae. Different parts of the plants were used by local people to cure several diseases including snakebites, cough, cold, and some other infectious diseases. It was observed that local people of Nargu Wildlife Sanctuary are still dependent on wild medicinal plants for the treatment of various diseases, and proper conservation planning is therefore needed to conserve these useful plant species in this region.
Keywords: Ethnobotany, traditional uses, medicinal plants, Nargu Wildlife Sanctuary.